A Socio-demographic Survey on Infertile Couples of Selected Villages in Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Infertility is a public health issue; it is defined as not having conceived after one year of unprotected sexual intercourse. In developing countries, there are severe social, psychological and economic consequences for infertile men and women.Objectives: This study was designed to find out socio-demographic attributes and treatment seeking pattern about the infertile couple (either of the couple).Materials and Methods: This survey was carried out in some selected villages of Ashulia, Saturia and Baliati of Dhamrai Upazilla in Dhaka. A total of 52 couples were included in the study. Purposive sampling technique was adopted. Couple who gave consent to participate in the study was interviewed. A structured questionnaire was used to collect the relevant information. Data were analyzed later on.Results: Among husbands 18(34.6%) were between age 40-49 years, 16(30.8%) were in the age group 30-39 years, 14(26.9%) were in the age group 20-29 years. Regarding age of the wives, majority, 32(61.5%) were in the age group 20-29 years, 14(26.9%) had age 30-39 years and rest 6(11.6%) were in the age group 40-49 years. About education of the husbands it was seen that 20(38.5%) passed SSC, 14(26.9%) had education from class VI to class X and 6(11.5%) were illiterates. Among wives, 32(61.4%) had education on class VI to class X, 10(19.2%) had primary level of education, 4(7.7%) were illiterates. Thirty four (65.4%) couples lived in nuclear families, 16(30.8%) were joint families and the rest 2(3.8%) were extended families. Twenty eight (53.8%) of the couples had marital life >10 years, 20(38.5%) had 6-10 years and the rest 4(7.7%) had marital life of 1-5 years. About 16(31%) had monthly income 5001-10000 taka, 10(19.2%) had 15001-20000 taka, another 10(19.2% had >20000 taka, 16(30.8%) had 5001-10000 taka and 2(3.8%) had monthly income upto 5000 taka. Twenty (38%) husband were involved in business and 44(76%) wives are house wives. Thirty two (61.5%) couple used contraceptives. Forty two (80.8/%) couples sought for treatment.Conclusion: In developing countries, Infertility has profound effects on individuals as the production of children is often highly socially valued and is vital for social security and for family income generation. National level active planning is needed to overcome this social problem.Journal of Armed Forces Medical College Bangladesh Vol.11(1) 2015: 25-29